Utilizing Peer Review and Revision in STEM to Support the Development of Conceptual Knowledge Through Writing. (July 2021) - Finkenstaedt-Quinn, Solaire A.; Polakowski, Noelle; Gunderson, Brenda; Shultz, Ginger V.; Gere, Anne Ruggles
While many STEM faculty believe Writing-to-Learn to be an effective instructional tool, instructional barriers such as the time and effort required to provide substantive feedback to their students limit the use of writing in STEM classrooms. Incorporating peer review and revision into the writing process can help mitigate these barriers while additionally supporting the learning process. This study presents an analysis of a Writing-to-Learn assignment that incorporates peer review and revision into a large introductory statistics course, where this study specifically focused on whether engaging with these processes results in changes in how students write about the content targeted by the assignment. Our results demonstrate that students made content-focused revisions between drafts that increased the amount of content they explained correctly. Additionally, our study provides evidence that students benefit from reading peers' work in a content-focused peer review and revision process. Overall, this study shows that incorporating peer review and revision into writing assignments focused on developing content knowledge provides students with substantive feedback and enhances students' conceptual learning.